1989
DOI: 10.1086/261617
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Discrimination and Self-Employment

Abstract: Census data, we find that observed differences in the self-employment income distributions are consistent with the theoretical predictions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
108
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 329 publications
(113 citation statements)
references
References 5 publications
4
108
0
1
Order By: Relevance
“…Non-Muslim employees may have reduced their cooperation with Arab and Muslim coworkers, which may have harmed employee productivity, particularly that of Arabs and Muslims. Finally, customer prejudice may have lowered the productivity of Arab and Muslim employees in occupations with direct customer contact (for example, retail, self-employment), if customers shied away from doing business where they had to interact with an Arab or Muslim person (Borjas and Bronars 1989;Nardinelli and Simon 1990). In sum, greater prejudice toward Arab and Muslim persons may have resulted in a decrease in the demand for Arab and Muslim labor, which would have lowered their wages and may have reduced their employment (or hours) depending on the elasticity of supply of labor.…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…Non-Muslim employees may have reduced their cooperation with Arab and Muslim coworkers, which may have harmed employee productivity, particularly that of Arabs and Muslims. Finally, customer prejudice may have lowered the productivity of Arab and Muslim employees in occupations with direct customer contact (for example, retail, self-employment), if customers shied away from doing business where they had to interact with an Arab or Muslim person (Borjas and Bronars 1989;Nardinelli and Simon 1990). In sum, greater prejudice toward Arab and Muslim persons may have resulted in a decrease in the demand for Arab and Muslim labor, which would have lowered their wages and may have reduced their employment (or hours) depending on the elasticity of supply of labor.…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“… 7 For similar arguments about self-selection and discrimination in other contexts, see Longhofer and Peters, 2005 (credit markets); and Borjas & Bronars, 1989 (self-employment). …”
mentioning
confidence: 99%
“…By 2006, according to a survey data, study education of rural labor force selfemployment have a positive impact [6], while Lazear also found that people who have multiple jobs and education background than people who work in the single or professional are more likely to become entrepreneurs themselves [7], Borjas study found that high degree of education of the individual than the low degree of education of individuals are more likely to enter self-employment activities [8].…”
Section: Personal Characteristicsmentioning
confidence: 99%